Small molecule-mediated regenerative engineering for craniofacial and dentoalveolar bone - Mitchell, Juan; Lo, Kevin W. H. (Frontiers in Bioengineering and Biotechnology, 2022)
The comprehensive reconstruction of extensive craniofacial and dentoalveolar defects remains a major clinical challenge to this day, especially in complex medical cases involving cancer, cranioplasty, and traumatic injury. Currently, osteogenic small molecule-based compounds have been explored extensively to repair and regenerate bone tissue because of their unique advantages. Over the past few years, a number of small molecules with the potential of craniofacial and periodontal bone tissue regeneration have been reported in literature. In this review, we discuss current progress using small molecules to regulate cranial and periodontal bone regeneration. Future directions of craniofacial bone regenerative engineering using the small molecule-based compounds will be discussed as well.